Mesarites as a source: then and now. (4th April 2016) - Angold, Michael
Abstract : I am guessing, but I suspect that Bryer's first introduction to Nicholas Mesarites was like mine through a very short article by A. A. Vasiliev, entitled 'Mesarites as a source', 1 which was a footnote to his much more substantial 'The foundation of the Empire of Trebizond', 2 which dominated the field for years. Vasiliev was responding to a criticism by Franz Dölger, who suggested that Vasiliev might have benefited from a perusal of the works of Nicholas Mesarites, which had been edited by his old master August Heisenberg. 3 Vasiliev was adamant Nicholas Mesarites had little to contribute to the early history of the Empire of Trebizond. In his opinion, the Seljuq inscription from the walls of Sinope, which Heisenberg included in his commentary, was far more valuable than anything that could be gleaned from Mesarites' writings. This rather explains why they remained a neglected source.